ANALISIS IMPLEMENTASI PENGELOLAAN ASET TETAP BERDASARKAN PERMENDAGRI NO. 7 TAHUN 2024 DI DINAS PEKERJAAN UMUM DAN TATA RUANG KABUPATEN BULELENG - Ihfadna Al Insani; Desak Nyoman Sri Werastuti; Ni Luh Gede Erni Sulindawati (Vokasi : Jurnal Riset Akuntansi, 2025)
Fixed assets owned by regional governments require special attention in their management due to the ongoing issues that indicate the need for evaluation and improvement to ensure compliance with applicable regulations. This study aims to analyze the management of fixed assets at Dinas Pekerjaan Umum dan Tata Ruang Kabupaten Buleleng based on Permendagri No. 7 Tahun 2024. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation. The results show that the Dinas PUTR Kabupaten Buleleng has implemented fixed asset management following the eleven stages stipulated in Permendagri No. 7 Tahun 2024, including needs planning and budgeting; procurement; utilization; safeguarding and maintenance; appraisal; transfer; disposal; elimination; administration; as well as guidance, supervision, and control. The implementation also reflects the foundational principles of asset management. This achievement is supported by several enabling factors, including effective interdepartmental communication, the use of the SIPD system to streamline tasks, proactive personnel disposition, and a clear bureaucratic structure, which collectively enhance asset management effectiveness. However, despite compliance with regulations, Dinas PUTR Kabupaten Buleleng still faces several challenges in practice, including limited human resources and weak oversight. Therefore, it is necessary to improve staff capacity, strengthen internal control and supervision systems, and optimize the use of information technology to ensure that fixed asset management becomes more efficient, effective, accountable, and transparent.